Appraisal of Triglyceride-Related Markers as Early Predictors of Metabolic Outcomes in the PREVIEW Lifestyle Intervention: A Controlled Post-hoc Trial - Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Siig Vestentoft, Pia; Brand-Miller, Jennie C.; Jalo, Elli; Westerterp-Plantenga, Margriet; Simpson, Elizabeth J.; Handjieva-Darlenska, Teodora; Stratton, Gareth; Huttunen-Lenz, Maija; Lam, Tony; Muirhead, Roslyn; et al. (Frontiers in Nutrition, 2021)
Background: Individuals with prediabetes are commonly overweight and benefit from dietary and physical activity strategies aimed at decreasing body weight and hyperglycemia. Early insulin resistance can be estimated via the Triglyceride Glucose Index (TyG = Ln [TG (mg/dl) × FPG (mg/dl)/2]) and the hypertriglyceridemic-high waist phenotype (TyG-waist), based on TyG x waist circumference measurements. Both indices may be useful for implementing personalized metabolic management. In this secondary analysis of a randomized controlled trial (RCT), we aimed to determine whether differences in baseline TyG values and TyG-waist phenotype predicted individual responses to a type-2 diabetes (T2D) prevention program. Methods: The present post-hoc analyses were conducted within the PREVIEW study completers (n=899), a multi-centre RCT conducted in eight countries (NCT01777893). The study aimed to reduce the incidence of T2D in a population with prediabetes during a 3-year randomized intervention with two sequential phases. The first phase was a 2-month weight loss intervention to achieve ≥ 8% weight loss. The second phase was a 34-month weight loss maintenance intervention with two diets providing different amounts of protein and different glycemic index, and two physical activity programs with different exercise intensities in a 2x2 factorial design. On investigation days, we assessed anthropometrics, glucose/lipid metabolism markers and diet and exercise questionnaires under standardized procedures. Results: Diabetes-related markers improved during all four lifestyle interventions. Higher baseline TyG index (p<0.001) was associated with greater reductions in body weight, fasting glucose and TG, while a high TyG-waist phenotype predicted better TG responses, particularly in those randomized to physical activity of moderate intensity. Conclusions: Two novel indices of insulin resistance (TyG and TyG-waist) may allow for a more personalized approach to avoiding progression to T2D. The PREVIEW study was registered at clinicaltrials.gov with reference: NCT01777893 (https://clinicaltrials.gov/ct2/show/NCT01777893).